2011
DOI: 10.1177/0267659111419272
|View full text |Cite
|
Sign up to set email alerts
|

Direct oxymetric peripheral tissue perfusion monitoring during open heart surgery with the use of cardiopulmonary bypass: preliminary experience

Abstract: The result of this first measurement seems to demonstrate that the standard technique of conducting cardiopulmonary bypass produces low muscle oxygen tension and, thus, little perfusion of skeletal muscle. The data also indicate that both high mean arterial blood pressure and high flow are necessary during CPB to ensure skeletal muscle perfusion. The investigation is continuing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Even if autoregulation system well regulates to maintain peripheral tissue circulation, CPB perfusion pressure seems to be more important to prevent peripheral tissue hypoperfusion under nonpulsatile flow. Recently, study suggested that not only high perfusion flow but also high perfusion pressure was necessary during CPB to protect the skeletal muscle [ 20 ]. It remains controversial which is more important for management of CPB, pressure, or flow.…”
Section: Resultsmentioning
confidence: 99%
“…Even if autoregulation system well regulates to maintain peripheral tissue circulation, CPB perfusion pressure seems to be more important to prevent peripheral tissue hypoperfusion under nonpulsatile flow. Recently, study suggested that not only high perfusion flow but also high perfusion pressure was necessary during CPB to protect the skeletal muscle [ 20 ]. It remains controversial which is more important for management of CPB, pressure, or flow.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, these methods rely on adequate perfusion to deliver the desired changes to the local surgical area, which can be difficult to achieve during an operation. A preliminary study, looking at tissue perfusion during surgery, reported a decrease in tissue perfusion and oxygen tension following the administration of anaesthetics [ 14 ]. Therefore, a locally targeted intervention that could increase local wound perfusion, and thus oxygenation, may be more clinically successful in surgical patients.…”
Section: Introductionmentioning
confidence: 99%